A study on the value of the relationship between newly occurring microinfarctions after stent-assisted treatment for unruptured intracranial aneurysms and systemic inflammatory immune indices - Lv, Yifan; Zhang, Tao; Li, Lei; Han, Guanda; Xu, Decai; Jiang, Zhiquan; Li, Jian (Frontiers in Neurology, 2025)
BackgroundA paucity of studies has been conducted on the relationship between new microinfarctions following stent-assisted treatment for unruptured intracranial aneurysms (UIA) and systemic inflammatory indices (SII) derived from complete blood counts (CBC) and clinical outcomes. The objective of this study was to assess the possible relationship between SII and the occurrence of new postoperative infarcts.MethodsA total of 64 patients who underwent UIA stent-assisted therapy at the Department of Neurosurgery, First Affiliated Hospital of Bengbu Medical University, from January 2024 to July 2025 were selected as the study subjects. Blood tests, systemic inflammatory markers [NMP: (Neutrophil Count* Monocyte Count), PLR: (Platelet count/Lymphocyte count), SII: ((Neutrophil Count*Platelet Count)/Lymphocyte Count)], and cranial MRI-DWI were collected at admission and on the third day post-surgery. Patients were divided into two groups, positive and negative, based on the presence of new microinfarctions.ResultsAmong the 64 patients included in the study, 24 (37.5%) MRI-DWI reveals new microinfarcts, while 40 (62.5%) MRI-DWI showed no evidence of new microinfarcts. A comparative analysis of the third day postoperatively reveals that white blood cell count, neutrophil count, PLR, and SII increased, while lymphocyte count decreased. The neutrophil count, lymphocyte count, PLR, and SII on the third day postoperatively were found to be associated with the occurrence of new microinfarctions. Third-day SII was independently correlated with new microinfarctions that occurred after UIA stent-assisted therapy.ConclusionSII may serve as a potential indicator of the association between postoperative inflammatory response and microinfarction events, with elevated postoperative SII levels correlating with the occurrence of new microinfarctions following UIA stenting procedures.